Diabetes mellitus in pregnancy and obstetrics outcome - Eva Febia; . Rajuddin (Syiah Kuala University, 2012)
Diabetes mellitus in pregnancy was associated with maternal and neonatal mortality and morbidity. This paper was purposed to assess the several cases of diabetes mellitus in pregnancy that were managed in Zainoel Abidin Hospital, Banda Aceh. There were ten cases of diabetes mellitus in pregnancy in Obstetrics Department Zainoel Abidin Hospital, Banda Aceh. Obstetrics outcomes were noted which include cesarean section, fetal distress, macrosomia, intra uterine fetal death, neonatal hypoglycemia, and neonatal death. We also explained patophysiology of diabetes mellitus in pregnancy, delivery, obstetrics complications, and neonatal complications. It was concluded that diabetes mellitus in pregnancy was associated with increased rate of obstetrics and neonatal mortality and morbidity